Mechanical properties of concrete containing POFA and EPS as replacement materials - Bahari, Nur Aishah Zafirah; Osman, Mohamad Hairi; Mahyeddin, Mohd Eizzuddin (Penerbit UTHM, 2021)
To solve the problems of increase in amount of the oil palm waste and expanded polystyrene, high emission of carbon dioxide and high density or normal concrete, a research of replacing cement and fine aggregate with expanded polystyrene (EPS) and palm oil fuel ash (POFA) were done. Few cylinders concrete with 150 mm diameter and 300 mm height were created using Simulia Abaqus CAE. These cylinders concrete was set with different materials which are 0.00 % POFA with 10.00 % to 30.00 % EPS, 10.00 % POFA with 0.00 % to 30.00 % EPS and 20.00 % POFA with 0.00 % to 30.00 % EPS. The main purpose of this study was to determine the mechanical properties of concrete containing EPS and POFA as replacement materials, determine the optimum percentage of EPS and POFA as the replacement materials in concrete and determine the maximum stress for concrete with 20.00 % POFA and 30.00 % EPS. From this paper, concluded that optimum percentage of POFA is 20.00 % while EPS is 30.00 % as replacement materials in concrete.To solve the problems of increase in amount of the oil palm waste and expanded polystyrene, high emission of carbon dioxide and high density or normal concrete, a research of replacing cement and fine aggregate with expanded polystyrene (EPS) and palm oil fuel ash (POFA) were done. Few cylinders concrete with 150 mm diameter and 300 mm height were created using Simulia Abaqus CAE. These cylinders concrete was set with different materials which are 0.00 % POFA with 10.00 % to 30.00 % EPS, 10.00 % POFA with 0.00 % to 30.00 % EPS and 20.00 % POFA with 0.00 % to 30.00 % EPS. The main purpose of this study was to determine the mechanical properties of concrete containing EPS and POFA as replacement materials, determine the optimum percentage of EPS and POFA as the replacement materials in concrete and determine the maximum stress for concrete with 20.00 % POFA and 30.00 % EPS. From this paper, concluded that optimum percentage of POFA is 20.00 % while EPS is 30.00 % as replacement materials in concrete.